Efektivitas pemberian biskuit mocaf (modified cassava flour) dengan penambahan bayam (spinacia oleracea) dan ikan teri (stolephorus sp) terhadap peningkatan kadar hemoglobin ibu hamil - Hadriani Irwan; Darmiati Darmiati (Holistik Jurnal Kesehatan, 2021)
Nutritional Value of Cookies made from the mixture of Mocaf flour (Modified Cassava Flour), spinach (spinacia oleracea) and anchovy (stolephorus sp) on the increase in hemoglobin levels on pregnant womenBackground: Anemia in pregnancy occurs due to an increase in blood plasma volume. The high rate of anemia is caused by the lack of awareness of a pregnant woman to improve nutritional status that occurs during pregnancy. Purpose: To determine the nutritional value of cookies made from the mixture of mocaf flour (modified cassava flour), spinach (spinacia oleracea) and anchovy (stolephorus sp) on the increase in hemoglobin levels of pregnant womenMethod: Quasi-experiment with one group pre and post-test design. The evaluation uses laboratory tests in the form of blood sampling to see the results of HB levels at the beginning and after treatment or intervention. The intervention was by giving mocaf biscuits (Modified Cassava Flour) with the addition of spinach (Spinacia oleracea) and anchovies (Stolephorus Sp) for 1 month to pregnant women at the Panambungan Health Center Makassar in May-June 2020 with a total sampling of 31 participants (pregnant women who have anemia). All ingredients for the intervention have been tested for nutritional content and safety at the STIKes Pelamonia Makassar laboratory. The population in this study were all pregnant women with anemia at the Panambungan Public Health Center, Makassar.Results: Finding an analysis with test-t-tests. The hemoglobin level of pre-intervention on an average of 8.7 g/dl, while after the intervention of 9.6 g/dl on average and it is known that a significant with p-value = 0.01Conclusion: The effect of the nutritional value of cookies made from the mixture of mocaf flour (modified cassava flour), spinach (spinacia oleracea) and anchovy (stolephorus sp) on the increase in hemoglobin levels on pregnant womenKeywords: Nutritional Value; Mocaf flour (Modified cassava flour); Spinach (Spinacia oleracea); Anchovy (Stolephorus sp); Hemoglobin levels; Pregnant womenPendahuluan: Anemia pada kehamilan terjadi karena terjadi peningkatan volume plasma darah. Kasus yang tinggi disebabkan oleh rendahnya kesadaran ibu hamil untuk meningkatkan status gizi yang terjadi pada selama masa kehamilan.Tujuan: Untuk mengetahui efektivitas pemberian biskuit mocaf (Modified Cassava Flour) dengan penambahan bayam (Spinacia Oleracea) dan ikan teri (Stolephorus Sp) terhadap peningkatan kadar hemoglobin ibu hamil di Puskesmas Panambungan Makassar.Metode: Quasi eksperimen dengan desain one group pre and post test. Evaluasinya menggunakan uji laboratorium berupa pengambilan darah untuk melihat hasil kadar HB diawal dan sesudah perlakuan atau intervensi. Intervensinya dengan pemberian biskuit mocaf (Modified Cassava Flour) dengan penambahan bayam (Spinacia Oleracea) dan ikan teri (Stolephorus Sp) selama 1 bulan kepada ibu hamil di Puskesmas Panambungan Makassar bulan mei-juni 2020 dengan cara total Sampling sebanyak 31 partisipan (para ibu hamil yang mengalami anemia). Semua bahan untuk intervensinya telah dilakukan uji kandungan gizi dan keamanannya di laboratorium STIKes Pelamonia Makassar. Populasi dalam penelitian ini adalah seluruh ibu hamil yang mengalami anemia di Puskesmas Panambungan Makassar.Hasil: Kadar hemoglobin pada responden sebelum diberikan biskuit didapatkan rata-rata sebesar 8.7 g/dl, sedangkan sesudah mengkonsumsi biskuit rata-rata sebesar 9.6 g/dl dan diketahui bahwa nilai  p = 001  signifikan yang berarti lebih kecil dari 0.05.Simpulan: Terdapat pengaruh pemberian biskuit mocaf (Modified Cassava Flour) dengan penambahan bayam (Spinacia Oleracea) dan ikan teri (Stolephorus Sp) terhadap peningkatan kadar hemoglobin ibu hamil di Puskesmas Panambungan Makassar.